Aspects of Cardio protection of Patients with Chronic Heart Failure, as a Consequence of Myocardial Infarction - Pulatov Shukhrat Shulopovich; Ruzieva Amira Asrorovna; Nizamova Nigora Gaffor kizi; Khasanzhanova Farida Odylovna (Genius Journals, 2023)
The purpose to study the effect of the myocardoprotector trimetazidine in patients with myocardial infarction complicated by chronic heart failure.
Keywords: myocardial infarction; coronary heart disease